Typology of Kampala Declaration Activities - Ulimwengu, John M. (International Food Policy Research Institute, 2025)
Key messages 1. The Kampala Declaration promotes multilevel coherence in agrifood systems investment by aligning National Agricultural Investment Plans (NAIPs) and Regional Agricultural Investment Plans (RAIPs) across Africa. 2. The green–yellow–blue typology employed in this brief is a critical innovation that helps classify and harmonize activities by their governance level—national (blue), regional/ REC (green), and continental/multi-REC (yellow). 3. A majority of activities (132) identified in the CAADP Strategy and Action Plan 2026–2035 are multilevel (green + yellow + blue), indicating broad intent for integrated implementation, but also emphasizing the need for strong coordination among all governance tiers. 4. Blue-only activities (74) dominate, revealing a tendency toward national responsibility, which still needs to be strategically aligned with REC and African Union (AU) initiatives. 5. Continental leadership remains weak, with few AU-led (yellow-only) initiatives, suggesting a policy gap in pan-African coordination and oversight—particularly in inclusivity, financing, and resilience. 6. Governance and trade-related interventions show the highest levels of harmonization, making them potential models for other domains such as food security, inclusivity, and climate resilience. 7. Inclusivity and resilience are under-prioritized at the regional and continental levels, requiring policy reframing that treats them as shared public goods rather than local concerns. 8. RECs are pivotal to the successful implementation of CAADP Agenda but are under- resourced, requiring enhanced mandates, planning tools, and inter-REC collaboration to execute cross-border and multicountry initiatives effectively. 9. Successful implementation hinges on institutional reforms, sustained political will, and capacity building, ensuring the Declaration translates into real, coherent, and transformative action across Africa’s agrifood systems. CAADP KAMPALA DECLARATION POLICY NOTE 3 AUGUST